Peningkatan Akses dan Praktik Pemberian Bantuan Hukum bagi Masyarakat di Desa Deme Dua dan Desa Bubalango - Dince Aisa Kodai; Roy Marthen Moonti (ABDI KARYA : Pengabdian Kepada Masyarakat, 2025)
Access to legal aid is a fundamental right guaranteed by Law No. 16/2011. However, in rural areas such as Deme Dua Village and Bubalango Village, limited infrastructure, low legal literacy, and lack of legal aid institutions are still the main obstacles. This study aims to analyze the obstacles and strategies to improve access to legal aid for the community in the two villages. The research method used is a juridical-empirical approach, by analyzing laws and regulations and conducting empirical studies on the implementation of legal aid in the field. The results show that the main challenges lie in the lack of legal aid organizations, complicated administrative procedures, and public distrust of the legal system. As a solution, this research recommends strengthening the role of paralegals, providing village-based legal aid services, and utilizing digital technology to expand access to legal information. With this strategy, it is hoped that access to justice for the poor can be better guaranteed.